Viscoelastic model for bending process of continuous fiber-reinforced thermoplastic sheets - Abadi, M.T. (Archives of Mechanics, 2025)
This paper presents an analysis of the bending process in thermoplastic sheets reinforced with unidirectional continuous fibers. To capture the material’s viscoelastic response during the bending process, a novel viscoelastic model is described based on the concept of transient reversible networks. The model incorporates kinematic constraints of material incompressibility and fiber inextensibility during deformation of the composite sheets. An analytical solution is derived, enabling the determination of the deformed geometry and bending forces as time-dependent functions of the bending angle, the deformation rate, and material parameters. The model’s performance is evaluated through comparisons with existing experimental data and a prior viscous model for bending process at various deformation rates. This comparison aids in identifying the material parameters and characteristic time associated with the transient reversible networks.